Mass exhumation and deposition of Mulinia lateralis (Bivalvia: Mactridae) on an intertidal beach, St. Catherines Island, Georgia, USA - Cleveland, C.M.; Prezant, Robert; Rollins, Harold; Toll, R.; Wylie, J. (Veliger -Berkeley-, 2002)
Episodic events which affect populations of marine invertebrate species are rarely documented. We report the catastrophic mass exhumation and deposition of a large aggregation of adult bivalves (Mulinia lateralis [Say, 1822]) to a suboptimal habitat on a sandy intertidal beach of St. Catherines Island, Georgia, USA. The displaced population impacted a large area (7000 m2) of the beach and consisted of similar-sized clams (∼ 13 mm mean shell length). We suggest that the exhumation could have been a result of storm-induced shear stress, an hypoxic event, or other environmental stress on the individuals. Events of this type could have important implications for population dynamics and cohort distribution, fisheries predictions and harvests, and interpretation of fossil assemblages.
Keywords: dept.aa; ⛔ No DOI found

Mollusca of Assateague Island, Maryland and Virginia: Additions to the fauna, range extensions, and gigantism - Prezant, Robert; III, C.L.; Chapman, E.J. (Veliger, 2002)
Collections of 108 species of marine and estuarine mollusks from and around Assateague Island, Maryland and Virginia, from 1991 to 1996, vary from and extend the known species lists generated by three previously published collections over the past 100 years. Extensive sampling, including benthic grabs, trawls, and hand collecting, has added 54 species of mollusks (20 bivalves, 31 gastropods, one polyplacophoran, and two cephalopods) to the 1914 list of Henderson & Bartsch and 46 (19 bivalves, 26 gastropods and one cephalopod) to that of Counts & Bashore from 1991. Homer et al. in 1997 provided a mollusk survey of Maryland coast bays and listed 73 molluscan species (including 10 species recorded as shells only and eight as taxonomic uncertainties). To the latter we have added 51 molluscan taxa they did not find (19 bivalves, 29 gastropods, one polyplacophoran, and two cephalopods). All collections represent a total described malacofauna of this region of 146 shallow-water species excluding undescribed or non-described taxa in earlier papers. Within the populations of some of the species collected were a few exceptionally large individuals, adding to previous records of unusually large specimens of mollusks from this region of the Atlantic coast. Additionally, some species of mollusks (Tectura testudinalis, Eupleura semisulcata [Gastropoda], Tridonta borealis [Bivalvia]) and some non-mollusks (the ascidian Ecteinascidia turbinata and a confirmation of an extension of the anthozoan Peachia parasitica) have been found in the waters surrounding Assateague, well outside of their previously reported geographic ranges. The results of the present study suggest the need for a re-evaluation of possible environmental shifts that could have taken place since the collections of the early 1900s and have elsewhere been implicated in the change of malacofauna of Assateague Island since that time. Additionally, range extensions reported could reflect a subtle geographic transition zone, newly introduced species, or, most likely, an understudied coastal area.
Keywords: dept.aa; ⛔ No DOI found

Marine Macroinvertebrate Diversity of St. Catherines Island, Georgia - Prezant, Robert; TOLL, RONALD; Rollins, Harold; CHAPMAN, ERIC (American Museum Novitates, 2002)
St. Catherines Island is one of several barrier islands lining the coast of Georgia, USA. This island is among the least recently anthropogenically impacted of the Georgia Sea Islands, but had not previously been examined in detail for coastal invertebrate macrofauna. From 1992 through late 1998 a coastal survey was conducted that examined the diverse marine invertebrate fauna of St. Catherines Island. Salt marshes, sand flats, mid- to low-energy sand beaches, beach wood debris, tidal creeks, shallow benthos, and artificial hard substrata (including docks) were qualitatively sampled for macroinvertebrates. Over 340 species were identified. Crustaceans composed close to 40% (14% amphipods; 15% decapods), polychaetes 17.5%, and molluscs about 25% of all species recovered. These results are compared to the few other relevant studies from the United States mid-Atlantic Coast.
5 citations (Crossref) [2023-10-31]
Keywords: dept.aa

A novel method for locating tagged infaunal bivalves: Submersible pulse technology metal detectors - Toll, R.B.; Prezant, Robert; Rollins, Harold (Journal of Shellfish Research, 2002)
Hardelams, Mercenaria mercenaria (Linne, 1758), tagged with brass washers attached to the outer shell surface and replanted into their natural habitat, were located remotely through the use of a commercially available, fully submersible, pulse technology metal detector. The ability to remotely locate tagged, replanted clams can increase the speed and efficiency of field operations associated with studies of clam population dynamics. Also, this methodology can reduce localized disturbances to the habitat that routinely accompany extensive hand probing to relocate experimental clams in traditional tag and recapture based studies.
Keywords: dept.aa; ⛔ No DOI found